The NordICC Study: Rationale and design of a randomized trial on colonoscopy screening for colorectal cancer - Kaminski, M. F.; Bretthauer, M.; Zauber, A. G.; Kuipers, E. J.; Adami, H.-O.; van Ballegooijen, M.; Regula, J.; van Leerdam, M.; Stefansson, T.; Påhlman, L.; Dekker, E.; Hernán, M. A.; Garborg, K.; Hoff, G.; null (Endoscopy, 2012)
Background and study aim: While colonoscopy screening is widely used in several European countries and the United States, there are no randomized trials to quantify its benefits. The Nordic-European Initiative on Colorectal Cancer (NordICC) is a multinational, randomized controlled trial aiming at investigating the effect of colonoscopy screening on colorectal cancer (CRC) incidence and mortality. This paper describes the rationale and design of the NordICC trial.Study design: Men and women aged 55 to 64 years are drawn from the population registries in the participating countries and randomly assigned to either once-only colonoscopy screening with removal of all detected lesions, or no screening (standard of care in the trial regions). All individuals are followed for 15 years after inclusion using dedicated national registries. The primary end points of the trial are cumulative CRC-specific death and CRC incidence during 15 years of follow-up. Power analysis: We hypothesize a 50 % CRC mortality-reducing efficacy of the colonoscopy intervention and predict 50 % compliance, yielding a 25 % mortality reduction among those invited to screening. For 90 % power and a two-sided alpha level of 0.05, using a 2:1 randomization, 45 600 individuals will be randomized to control, and 22 800 individuals to the colonoscopy group. Interim analyses of the effect of colonoscopy on CRC incidence and mortality will be performed at 10-year follow-up.Conclusions: The aim of the NordICC trial is to quantify the effectiveness of population-based colonoscopy screening. This will allow development of evidence-based guidelines for CRC screening in the general population.Trial registration: NCT 00883792.